A CsMYB6-CsTRY module regulates fruit trichome initiation in cucumber. (8th February 2018) - Yang, Sen; Cai, Yanling; Liu, Xingwang; Dong, Mingming; Zhang, Yaqi; Chen, Shuying; Zhang, Wenbo; Li, Yujing; Tang, Min; Zhai, Xuling; Weng, Yiqun; Ren, Huazhong
Abstract : CsMYB6 interacts with CsTRY and they work cooperatively to suppress fruit trichome initiation in cucumber. Abstract: Fruit epidermal features such as the number and size of trichomes or spines are important fruit quality traits in cucumber production. Little is known about the molecular mechanisms underlying fruit spine formation in cucumber. Here, we report functional characterization of the cucumber CsMYB6 gene, which encodes a MIXTA-like MYB transcription factor that plays an important role in regulating fruit trichome development. Spatial-temporal expression analyses revealed high-level expression of CsMYB6 in the epidermis of cucumber ovaries during fruit spine initiation, which was similar to the expression of CsTRY, a homolog of the Arabidopsis TRY gene that also plays a key role in trichome development. Overexpression of CsMYB6 and CsTRY in cucumber and Arabidopsis revealed that CsMYB6 and CsTRY act as negative regulators of trichome initiation in both species, and that CsMYB6 acted upstream of CsTRY in this process. CsMYB6 was found to bind to the three MYB binding sites inside the promoter region of CsTRY, and protein–protein interaction assays suggested that CsTRY also directly interacted with CsMYB6 protein. The results also revealed conserved and divergent roles of CsMYB6 and its Arabidopsis homolog AtMYB106 in trichome development. Collectively, our results reveal a novel mechanism in which the CsMYB6-CsTRY complex negatively regulates fruit trichome formation in cucumber.